2017
DOI: 10.1080/09537104.2017.1316838
|View full text |Cite
|
Sign up to set email alerts
|

Platelet lysate as a serum replacement for skin cell culture on biomimetic PCL nanofibers

Abstract: Platelets are a popular source of native growth factors for tissue engineering applications. The aim of the study was to verify the use of platelet lysate as a fetal bovine serum (FBS) replacement for skin cell culture. The cytokine content of the platelet lysate was characterized using the Bio-Plex system. The cells (fibroblasts, melanocytes, and keratinocytes) were cultured on PCL nanofibrous scaffolds to mimic their natural microenvironment. The cytokine content of the platelet lysate was determined, and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 37 publications
4
22
0
Order By: Relevance
“…Furthermore, the samples contained a minimum of spherical defects. The stereology of the scaffolds was in accordance with other findings [14,15]. The scanning electron microscope also showed a fine fibrin network formed on the surface of the plateletfunctionalized samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, the samples contained a minimum of spherical defects. The stereology of the scaffolds was in accordance with other findings [14,15]. The scanning electron microscope also showed a fine fibrin network formed on the surface of the plateletfunctionalized samples.…”
Section: Discussionsupporting
confidence: 88%
“…The cell adhesion properties of PVA nanofibers could be improved using other polymers, such as chitosan [20], gelatin [21] or hyaluronic acid [22]. On the other hand, PCL was shown to be effective in fostering the culture of melanocyte, which is in accordance with previously published data [14,18]. The suitability of PCL as a substrate for melanocyte culture was described by Savkovic et al [23].…”
Section: Discussionsupporting
confidence: 81%
“…In the present study, the cytokine content of HPL was analyzed via a quantitative multiplex immunoassay to identify potentially relevant cytokines contributing to MSC osteogenesis. Although previous studies have measured cytokines in HPL via semi-quantitative assays [ 22 , 36 40 ], to our knowledge, only five studies have reported quantitative multiplex-based assessments [ 21 , 39 , 41 44 ]. Considerable differences in cytokine concentrations are observed across the different studies (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The best results were obtained in the centrifugally spun samples with the highest concentration of platelets (the highest tested concentration of platelet-derived molecules, C10). Nanofibers made of PCL, using electrospinning, were successfully used for the melanocyte culture [ 45 , 57 , 58 ]. Savkovic et al showed PCL nanofibers to be superior to a 2D cell culture substrate, in terms of melanin synthesis [ 57 ].…”
Section: Discussionmentioning
confidence: 99%